EVALUATION OF EFFECTIVENESS BASED ON THE ANALYSIS OF THE STRUCTURE AND ALGORITHMS OF STRING DATA - Toirov Bobirmirzo Nodir ugli (Web of Journals Publishing, 2024)
In data structures, a string is a sequence of characters used to represent text. Strings are commonly used in computer programs to store and manipulate textual data. They can be manipulated using various operations such as concatenation, substring extraction, and comparison.
Keywords: Encryption, hashing, pattern searching, naive string matching, KMP algorithm, Rabin-Karp algorithm, Boyer-Moore algorithm, Z-algorithm.